The synthesis of size-controlled 3C-SiC nanoflakes and their photoluminescent properties. (17th May 2016) - Fan, Xiujun; Ye, Ruquan; Peng, Zhiwei; Wang, Juanjuan; Fan, Ailing; Guo, Xia
Abstract: Size-controlled and high-purity 3C-SiC nanoflakes (NFs) are synthesized on the tips of vertically aligned carbon nanotube (VA-CNT) carpets with a hot-filament chemical vapor deposition (HF-CVD) method. The average diameter and height of SiC NFs can be tuned by changing the thickness of per-deposited Si and growth conditions. The growth process of the SiC NFs is suggested to be dominated by a vapor–solid (VS) mechanism. The prepared SiC NFs exhibit quantum-confinement effects, emitting strong violet-blue photoluminescence (PL) under ultraviolet excitation. The PL peak position changes from 410 to 416 nm as the excitation line increases from 290 to 400 nm. This result opens the possibility for the application of the luminescent solid-state freestanding 3C-SiC NFs in photonics as well as photonics/electronics integration.